Panic attack in the outpatient clinic of Emergency Medical Services in Belgrade - Slavoljub (Medicinski časopis, 2023)
Introduction: Panic attack is defined as specific, frightening experience of intense fear and impending catastrophe that is accompanied by numerous somatic symptoms. Scope: The scope of study was to show the presentation of panic attack disorder in patients in EMS Belgrade Ambulatory Clinic, its frequency, temporal patterns and prescribed therapy. Methodology: The research is a cross-sectional study of the work of a one general practitioner and a gerontology subspecialist from the City Institute outpatient clinic in Belgrade EMS, in the period from 18.12. 2014. to 16.01. 2019. In each patient’s medical record there was at least one or more complaints recorded. Results: Out of 8398 patients, 61 were found with a diagnosis of panic attack, which is 0.73% of the total number of examined patients. 50.82% were male and 49.18% female, with an average age of 39.92. The most common symptoms were respiratory, as well as numbness and tingling, dizziness, feelings of insecurity and fainting, In 80.3% of cases, patients had somewhat similar simptoms previously, whereas 31.1% presented with an actual panic attack. Of the total number of patients 21.3% of them have already been treated for anxiety and depressive disorder. Ten of them tried to help themselves by taking either bromazepam and diazepam tablets on their own, whereas 35.5% were actually prescribed diazepam by our staff physicians. Conclusion: Ppanic attack is most often presented as a respiratory manifastation. Patients call for medical assistance somewhat more frequently at nighttime when community healthcare centres are closed, however, this is of no statistical significance. The administered therapy was diazepam per os or intramuscularly.